Global sliding-mode control. Improved design for a brushless DC motor. - Hyeung-Sik Choi (IEEE Control systems magazine)
An improved global sliding-mode control (GSMC) was proposed for controlling second-order time-varying systems with bounded uncertain parameters and disturbances. The proposed controller drives the system states along the minimum time trajectory within the input torque limit. If the reference input and the bounds of the uncertain parameters and disturbances are specified, the minimum arrival time and the acceleration are expressed in closed-form equations. The proposed controller was applied to the brushless DC motor with uncertain loads. Experimental results of the proposed controller are quite similar to simulation and closed-form equation results and showed the best performance compared with other SMC. The closed-form equation can be used for designing motor-based actuators for mechanical systems without simulation and experiments